2019
DOI: 10.1002/anie.201912654
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecular Artificial Light‐Harvesting System with Two‐Step Sequential Energy Transfer for Photochemical Catalysis

Abstract: An artificial light‐harvesting system with sequential energy‐transfer process was fabricated based on a supramolecular strategy. Self‐assembled from the host–guest complex formed by water‐soluble pillar[5]arene (WP5), a bola‐type tetraphenylethylene‐functionalized dialkyl ammonium derivative (TPEDA), and two fluorescent dyes, Eosin Y (ESY) and Nile Red (NiR), the supramolecular vesicles achieve efficient energy transfer from the AIE guest TPEDA to ESY. ESY can function as a relay to further transfer the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(162 citation statements)
references
References 62 publications
3
148
1
3
Order By: Relevance
“… 2 In recent years, much attention has been focused by synthetic and material chemists to construct artificial LHSs via the FRET process which include conjugated polymers, porphyrin arrays, porous materials, dendrimers, and host–guest assemblies. 3 Among them supramolecular systems based on non-covalent interactions draw considerable attention in the synthesis of efficient FRET systems as they avoid a multistep synthetic process which is obligatory in the synthesis of scaffold covalent compounds. 4 Although some successful approaches were adopted for an efficient FRET process in supramolecular architectures based on covalent organic frameworks (COFs) 5 and metal organic frameworks (MOFs), 6 such systems are easy to synthesize but their poor solubility and stability in common solvents restrict their processability for further application.…”
Section: Introductionmentioning
confidence: 99%
“… 2 In recent years, much attention has been focused by synthetic and material chemists to construct artificial LHSs via the FRET process which include conjugated polymers, porphyrin arrays, porous materials, dendrimers, and host–guest assemblies. 3 Among them supramolecular systems based on non-covalent interactions draw considerable attention in the synthesis of efficient FRET systems as they avoid a multistep synthetic process which is obligatory in the synthesis of scaffold covalent compounds. 4 Although some successful approaches were adopted for an efficient FRET process in supramolecular architectures based on covalent organic frameworks (COFs) 5 and metal organic frameworks (MOFs), 6 such systems are easy to synthesize but their poor solubility and stability in common solvents restrict their processability for further application.…”
Section: Introductionmentioning
confidence: 99%
“…The 4 @TPEDA‐ESY‐NiR‐based nanoreactor was successfully applied for the photocatalytic dehalogenation of α‐bromoacetophenone in an aqueous medium (Figure 11). [40] Compared to the reactions with ESY+NiR fluorescent dyes (31 %) as well as a blank and TPEDA control, the photocatalytic performance of the nanoreactor was significantly improved, with an optimized yield of 96 %. This was attributed to two factors: first, the loading of the fluorescent dyes into the hydrophobic, self‐assembled vesicles minimize photobleaching, and second, aggregation‐induced emission of the donor and fluorescent dyes arranged within the confined space avoid fluorescent quenching.…”
Section: Pa‐based Nanomaterials For Catalysismentioning
confidence: 99%
“…Other impressive applications of ALHSs in aqueous environments have been reported. For example, Tang and coworkers reported that a conjugated polymeric supramolecular network based on AIEgen displays an ultrahigh antenna effect, [ 92a ] Wang and coworkers reported a supramolecular ALHS for photochemical catalysis, [ 98 ] and Diao and coworkers reported stimulus‐responsive light‐harvesting complexes with photocatalytic activity. [ 99 ] In terms of optical behavior regulation, the assemblies formed by CDs and CAs are evenly matched.…”
Section: Optical Behavior Researchmentioning
confidence: 99%